Rheological properties and structural characterization of salep improved by ethanol treatment - Kurt, Abdullah; Kahyaoglu, Talip (ELSEVIER SCI LTD, 2015)
Glucomannan is the main and important constituent of salep. The other contents are called as impurities. In this study, the removal of them was achieved by ethanol treatment to increase salep quality (40%, 50%, 60%, and 70%). The highest glucomannan and the lowest impurities contents were succeeded with the 40% ethanol treatment (SF40). Apparent viscosity of SF40 increased about 5 folds as compared with native salep. SF40 also had higher intrinsic viscosity [eta] and lower critical concentration (C*) than other samples. The improved molecular entanglement between glucomannan chains were demonstrated with increased Berry number C chi[eta]. The storage (G') and loss (G '') moduli spectra of SF40 were found higher within the whole range of frequency and temperature. This simple ethanol process could be used as a promising modification method for improving the properties of salep. (C)15 Elsevier Ltd. All rights reserved.
Keywords: Salep; Glucomannan; Rheology; Intrinsic viscosity; Morphology; KONJAC GLUCOMANNAN; RICE STARCH; GUM; TEMPERATURE; VISCOSITY; EXOPOLYSACCHARIDE; CHITOSAN; SLUDGE; Chemistry; Polymer Science